FAKTOR MANAJEMEN SUMBER DAYA MANUSIA (MSDM) DALAM PENERAPAN SISTIM MANAJEMEN LINGKUNGAN (SML) ISO 14001 DI PT RIAU ANDALAN PULP AND PAPER - Kasman Kasman; B Isyandi (Jurnal Ilmu Lingkungan, 2013)
This research aims to ascertain the influence of human resources management (HRM) whichis consist of commitment management, empowerment, feedback and review and reward to theEMS ISO 14001 performance. The results of multiple linear regression analysis using SPSS19 suggests that management commitiment, empowerment, feedback and review and rewardhave a siginificant positive relationship to EMS ISO 14001 performance with the coeficiencorelation accordingly 0.704, 0.695, 0.809 dan 0.702 . Feedback and review has thestrongest relationship to EMS ISO 14001 performance according to this coeficientcorrelation. The research aslo suggests that there is significant influence of commitmentmanagement to EMS ISO 14001 performance which is indicated by t-value 2.938 > t-tabel1.96, but there is no significant influence of empowerment to EMS ISO 14001 performance ast-value 1.092 < t-table 1.96, there is significant influence of feedback and review to EMSISO perfromance where the t-value 7.174 > t-table 1.96 and there is significant influence ofreward to EMS performance which is indicated by t-value 2.801 > t-table 1.96. Furthermore,the research suggest that simultaneously there is significant influece of managementcommitment, empowerment, feedback and review and reward to EMS performance using F-Test where F-value 130.018 > F-table 2,80 with the degree of significant 0.05 (5%). Usingdetermination coeficeint analysis it is found that R Square value (R2) is 0.691 or 69,1% thatmeans the infleunce of independent variable of commitment management, empowerment,feedback and review and reward is 69,1% while the rest are others factors which is notstudied.